1982
DOI: 10.1177/00220345820610062901
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Composites of Selected Shades

Abstract: The optical properties of seven shades of a conventional composite and five shades of a microfilled composite were determined from reflection spectrophotometric data with Kubelka's equations. Scattering and absorption coefficients decreased and values of infinite optical thickness increased as wavelength increased from 405 to 700 nm. Reflectivity curves were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 7 publications
1
14
1
Order By: Relevance
“…14 Previous study showed that the X 1 of restoration materials ranged from 4.19 to 6.70 mm, 10 while the X 1 of translucent composites in the present study were from 10.40 to 12.61 mm, which was much higher than the previous values. The possible reasons could be the special species of the translucent composites.…”
Section: [ ( F I G _ 4 ) T D $ F I G ]contrasting
confidence: 70%
See 2 more Smart Citations
“…14 Previous study showed that the X 1 of restoration materials ranged from 4.19 to 6.70 mm, 10 while the X 1 of translucent composites in the present study were from 10.40 to 12.61 mm, which was much higher than the previous values. The possible reasons could be the special species of the translucent composites.…”
Section: [ ( F I G _ 4 ) T D $ F I G ]contrasting
confidence: 70%
“…[10][11][12][13] The optical properties of materials could be mainly evaluated by the optical constants including scattering coefficient (S), absorption coefficient (K), light reflectivity (RI) and infinite optical thickness (X 1 ), and these values could be determined using Kubelka's equations. 10,11,14 S and K are wavelength-dependent coordinates which characterize the translucency and color of light scattering materials. 15,16 Light reflectivity (RI) indicates the light reflectance of a material of infinite thickness which might indicate the true color of translucent materials regardless of the thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is expected to affect the spectral values of other g-related optical properties. On the other hand, the refractive index of the material is important in determining the optical properties because it affects the reflection at the border lines caused by sample surface and filler particles or matrix, in the case of the dental-resin composites [49,50]. Particularly, for the dentalresin composites, since they are composed of inorganic filler particles immersed in an organic matrix, changes in the refractive index inside the material may have a substantial influence.…”
Section: Methodsmentioning
confidence: 99%
“…where R B is the reflectance of the black background, R W is the reflectance of the white background, R(B) is the light reflectance of the sample over the black background and R(W) is the light reflectance of the sample over the white background [18]. a ¼…”
Section: Kubelka-munk Coefficientsmentioning
confidence: 99%